CSNY/Déjà vu [videorecording (DVD)] - Young, Neil, 1945-; Colbert, Stephen, 1964- (LionsGate, 2008)
The war in Iraq is the backdrop as the Crosby, Stills, Nash and Young Freedom of Speech Tour crisscrosses North America. Echoes of Vietnam-era anti-war sentiment abound as the band connects with today's audiences.